Childhood Hypertension: A Retrospective Analysis of Causes, Treatments, and Complications - Mohamed S. Al Riyami; Aisha Al Shuaibi; Suad Al Jardani; Asma Elfar; Anisa Al Maskari; Badria Al Gaithi; Sulaiman Al Saidi; Naifain Al Kalbani (MDPI AG, 2024)
Background: Hypertension is prevalent in the pediatric population, with estimated rates between 2% and 5%, and its incidence is rising globally. This study offers a single-center analysis of hypertension in children. Methods: a retrospective chart review was conducted involving children aged 1 month to 13 years diagnosed with hypertension. Results: The study included a total of 129 children. Secondary hypertension was identified in 103 patients (79.8%), while primary hypertension was noted in 26 patients (20.2%). Primary hypertension was more common among pre-teen children (50.0%), whereas secondary hypertension predominantly affected those aged 1 to 5 years. Renal parenchymal disease emerged as the most frequent etiology of secondary hypertension, followed by endocrine disorders and vascular issues. No significant correlation was found between hypertension and obesity. The primary complications associated with hypertension in these children were cardiovascular, followed by neurological issues. A small proportion (14.7%) managed their hypertension solely through lifestyle modifications, while the majority required additional antihypertensive medications. At the final follow-up, 50% of the children demonstrated improved blood pressure readings. Conclusion: The findings indicate a higher prevalence of secondary hypertension compared to primary hypertension among the studied population. This study underscores the necessity for heightened awareness among pediatricians regarding the early identification and management of hypertension. Larger population-based studies are warranted to further investigate the prevalence, causes, and outcomes of hypertension in this region.